ИСПОЛЬЗОВАНИЕ ИНФОРМАЦИОННЫХ ТЕХНОЛОГИЙ ДЛЯ ПРЕПОДАВАНИЯ ФИЗИКИ В ШКОЛЬНОМ ОБРАЗОВАНИИ - Камалов, А.Б.; Нажиматдинова, Н.Ж. (SCIENCE and SOCIETY, 2025)
The article explores the potential of integrating information technologies in teaching the "Electrodynamics" section of high school physics. It highlights the advantages of using IT resources, such as virtual laboratories, simulations, and interactive materials, to enhance the effectiveness and accessibility of education. Examples of technology applications are provided, demonstrating how they aid in visualizing complex physical processes and fostering critical thinking and research skills among students.